2020
DOI: 10.1080/11038128.2020.1817544
|View full text |Cite
|
Sign up to set email alerts
|

Perceived job strain among Swedish occupational therapists with less than 10 years of work experience

Abstract: Background: Occupational therapists with less than 10 years of work experience have been shown to be at higher risk of work-related stress. There is a need for further research on the level of job strain they perceive. Aims: To investigate the perceived level of job strain among Swedish occupational therapists with less than 10 years of work experience and differences between groups who have worked for 0-5 years and 6-10 years. Material and methods: In this cross-sectional study, a web-based survey was sent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…To measure job strain, the DCSQ, an established self-reported tool to measure a stressful work environment, was used. The 17-item DCSQ includes the three scales of psychological demands (five items), decision latitude/or control (six items), and social support at work (six items) Each item is rated on a 4-point Likert scale, "Strongly disagree, " "Agree, " "Disagree, " and "Strongly agree" (range, 1-4) (37)(38)(39).…”
Section: The Demand Control Support Questionnairementioning
confidence: 99%
“…To measure job strain, the DCSQ, an established self-reported tool to measure a stressful work environment, was used. The 17-item DCSQ includes the three scales of psychological demands (five items), decision latitude/or control (six items), and social support at work (six items) Each item is rated on a 4-point Likert scale, "Strongly disagree, " "Agree, " "Disagree, " and "Strongly agree" (range, 1-4) (37)(38)(39).…”
Section: The Demand Control Support Questionnairementioning
confidence: 99%
“…Correspondingly, factors such as low workload, high control, high sense of community, and high justice in the organisational and social work environment have been shown to be associated with no or negligible stress symptoms [5]. The project has also revealed that the majority of occupational therapists with less than 10 years of experience report high control and high social support in their organisational and social work environment [10].…”
Section: Introductionmentioning
confidence: 97%